Infrared spectroscopy of methoxyphenols involved as atmospheric secondary organic aerosol precursors: Gas-phase vibrational cross-sections. (August 2016) - Cuisset, A.; Coeur, C.; Mouret, G.; Ahmad, W.; Tomas, A.; Pirali, O.
Abstract: Methoxyphenols are emitted in the atmosphere from biomass burning and recent works have shown the potential role of these oxygenated aromatic species in the formation of secondary organic aerosols. IR spectroscopic data that would enable their remote measurement in the atmosphere remain scarce in the literature. Room temperature Far-IR cross-sections of 4 methoxyphenols (2-methoxyphenol or guaiacol, 3-methoxyphenol, 4-methoxyphenol and 2, 6-dimethoxyphenol or syringol) have been determined using the THz synchrotron radiation available at SOLEIL. Mid- and near-IR regions have also been investigated with a conventional Fourier transform IR setup and allowed to provide a set of vibrational cross-sections of the studied methoxyphenols. Finally, gas-phase cross sections of two nitroguaiacol isomers (4-nitroguaiacol and 5-nitroguaiacol), two intermediate products involved in the formation of secondary organic aerosols have been measured in the mid- and near-IR with a heated multi-pass cell. Harmonic and anharmonic density functional theory calculations were carried out for all the studied compounds and allowed a full assignment of the recorded rovibrational bands. Highlights: Far-IR cross-sections of 4 methoxyphenols were measured using a THz synchrotron radiation. A complete set of fundamental vibrational cross-sections of 4 methoxyphenols is provided. Gas-phase cross sections of two nitroguaiacol isomers have been measured in a heated multi-pass cell. Harmonic and anharmonic DFT calculations were carried out allowing a full assignment of the spectra.